Losing my religion: Luther, and the so‐called new perspective on Paul vis‐à‐vis feminist interpretations of Paul. Issue 4 (22nd October 2022) - Pedersen, Else Marie Wiberg
Abstract: This article is based on a paper given on August 16 at the seminar "Losing my Religion" held in connection with the 14th International Congress for Luther Research: Word and World. It offers a heuristic analysis of different attacks on the reformer Martin Luther and Lutheran theology, both internally and externally, with a focus on the generalizing critique of what is at times labeled "the traditional (Protestant) confrontation perspective" by the so‐called new—or even radical—Paul New Testament scholars. It is demonstrated that the Paul readings, foremost Paul's letter to the Romans, by the new Paul perspective scholars can be aligned with the Paul readings made by radical feminist New Testament scholars, as both groups read the bible as history from an essentialist angle. By contrast, the attacked "traditional (Protestant) perspective" can be aligned with revisionist feminist New Testament scholars, as these latter groups read the bible as theology from a constructivist angle.